2017
DOI: 10.1103/physreva.95.063418
|View full text |Cite
|
Sign up to set email alerts
|

Searching for an optimal control in the presence of saddles on the quantum-mechanical observable landscape

Abstract: The broad success of theoretical and experimental quantum optimal control is intimately connected to the topology of the underlying control landscape. For several common quantum control goals, including the maximization of an observable expectation value, the landscape has been shown to lack local optima if three assumptions are satisfied: (i) the quantum system is controllable, (ii) the Jacobian of the map from the control field to the evolution operator is full-rank, and (iii) the control field is not constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 127 publications
1
16
0
Order By: Relevance
“…Recently, it has been shown that quantum alternating operator unitaries can perform universal quantum computation [3]. In the infinitesimal time setting, QAOA also encompasses the more general problem of the application of time varying quantum controls [4][5][6][7][8][9][10][11][12][13][14]. In this work, we study the quantum alternating operator formalism as a general framework of performing arbitrary unitary transformations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that quantum alternating operator unitaries can perform universal quantum computation [3]. In the infinitesimal time setting, QAOA also encompasses the more general problem of the application of time varying quantum controls [4][5][6][7][8][9][10][11][12][13][14]. In this work, we study the quantum alternating operator formalism as a general framework of performing arbitrary unitary transformations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we ask whether optimal learning sequences for performing the target unitary U can be obtained by using gradient descent optimization on the parameters t, τ of V( t, τ ). The matrices A, B are sampled from the Gaussian Unitary Ensemble (GUE) so that the algebra generated by A, B via commutation is with probability one complete in u(d), i.e., the system is controllable [4][5][6][7][8][9][10][11][12][13][14]. The parameters t, τ represent the times for which the generators of V( t, τ ) are applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the influence of saddles was systematically investigated in Ref. [59]. An extremal control problem was identified that contains a highly attractive saddle submanifold.…”
Section: Effect Of Saddle Pointsmentioning
confidence: 99%
“…2(a). There are additional saddle points on the landscape that may slow down the optimization, but they will not halt even a greedy algorithm search for global optimal solutions [13]. When the control resources are insufficient, e.g., when the control pulses have very limited time duration and bandwidth, false traps will emerge to likely halt the optimization procedure in a suboptimal minimum (Fig.…”
Section: Introductionmentioning
confidence: 99%